Pengaruh Metode Eksperimen terhadap Hasil Belajar IPA Ditinjau dari Keaktifan Siswa - Retno Utaminingsih; Muhammad Nizaar (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2020)
This research is descriptive aiming to find out the tendency of science learning outcomes and the activeness of fourth grade students of SD Negeri Banguntapan Bantul whose learning uses the experimental method and lecture method. Comparatively to find out the difference in science learning outcomes between learning using the experimental method and the lecture method in terms of the activeness of fourth grade students of SD Negeri Banguntapan, Bantul. The research method used quasi experiment with Nonequivalent Control Group Design. The research was conducted on the fourth grade students of SD Negeri Banguntapan, Bantul. Data collection techniques using test techniques, documentation techniques and questionnaire techniques. Data analysis techniques using anacova test after the analysis of the test requirements which include the test for the normality of the distribution, the homogeneity test of variance, and the linearity test. From the results of an anacova test it can be seen that the price of Fcount = 4.285 with p = 0.045 where p <0.05 so that it can be concluded that there are significant differences in the learning outcomes of science between those using the experimental method and the lecture method in terms of student activity. Because the average value of the class using the experimental method is higher than the average value of the class using the lecture method, so there is the influence of the experimental method on the science learning outcomes in terms of the activeness of the fourth grade students of SD Negeri Banguntapan, Bantul.